Pengaruh Self-Efficacy dan Toleransi Risiko terhadap Minat Hybrid Career Mahasiswa Solo: Peran Transformasi Digital Sebagai Moderasi - Andini, Devi (Journal of Economics and Business Research (JUEBIR), 2025)
This study aims to examine the effects of self-efficacy and risk tolerance on students’ interest in hybrid careers, as well as to investigate the moderating role of digital transformation. Using a quantitative approach, data were collected through an online questionnaire from 140 university students in the Solo region and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS) via SmartPLS. The results indicate that risk tolerance and digital transformation have a positive and significant effect on hybrid career interest. Furthermore, self-efficacy is found to significantly moderate the relationship between digital transformation and hybrid career interest with a negative interaction effect, whereas risk tolerance does not function as a moderating variable. These findings highlight the novelty of this study by demonstrating that psychological readiness does not always exert a direct influence but interacts contextually with the digital environment in shaping students’ career interests. This research provides important implications for universities and policymakers in designing digital-based career development strategies to better prepare students for the evolving labor market.